Silicon isotopes in meteorites and planetary core formation - Armytage, R; Georg, R; Savage, P; Williams, H; Halliday, A (2011)
The silicon (Si) isotope compositions of 42 meteorite and terrestrial samples have been determined using MC-ICPMS with the aim of resolving the current debate over their compositions and the implications for core formation. No systematic δ30Si differences are resolved between chondrites (δ30Si=-0.49±0.15‰, 2σSD) and achondrites (δ30Si=-0.47±0.11‰, 2σSD), although enstatite chondrites are consistently lighter (δ30Si=-0.63±0.07‰, 2σSD) in comparison to other meteorite groups. The data reported here for meteorites and terrestrial samples display an average difference Δ30SiBSE-meteorite*=0.15±0.10‰, which is consistent within uncertainty with previous studies. No effect from sample heterogeneity, preparation, chemistry or mass spectrometry can be identified as responsible for the reported differences between current datasets. The heavier composition of the bulk silicate Earth is consistent with previous conclusions that Si partitioned into the metal phase during metal-silicate equilibration at the time of core formation. Fixing the temperature of core formation to the peridotite liquidus and using an appropriate metal silicate fractionation factor (ε∼0.89), the Δ30SiBSE-meteorite* value from this study indicates that the Earth core contains at least 2.5 and possibly up to 16.8wt% Si. © 2011 Elsevier Ltd.